Kemampuan Berhitung Anak melalui Media Kartu Angka - Dina Marselani (Aṭfāluna: Journal of Islamic Early Childhood Education, 2019)
This research was conducted due to the low level of numeracy ability in children of group B in TK Kemala Bhayangkari 13 Padangsidimpuan. The formulation of the problem under study was how to improve children's numeracy skills through numeric media. The research conducted was classroom action research consisting of two observations, each of which consisted of 4 stages, namely planning, implementation, observation, and reflection. The subjects of this study were children of group B in TK Kemala Bhayangkari 13 Padangsidimpuan by using observation sheets. The data analysis used was qualitative data analysis techniques that can be seen from children's numeracy skills and quantitative data were calculated by formula. The results obtained in children's numeracy skills have increased. Before the action was taken, the level of numeracy ability of children was still very low, after the first cycle of research was obtained 44% and in the second cycle increased to 88%. After conducting research starting from pre-cycle, cycle I, cycle II, it was concluded that the numeracy ability of group B children in TK Kemala Bhayangkari 13 Padangsidimpuan had increased.